2002
DOI: 10.1007/s001090100274
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-S-transferase µ and theta gene polymorphisms as new risk factors of atopic bronchial asthma

Abstract: The genetic polymorphism of glutathione- S-transferase M1 (GSTM1) and glutathione- S-transferase T1 (GSTT1) genes and the cytochrome P4501A1 gene responsible for xenobiotic conjugating enzymes of the phase II and phase I detoxification system were studied by PCR-RFLP in the blood spots of 109 patients with atopic bronchial asthma and 90 healthy individuals. GSTM1 gene deletion (GSTM1(0/0)) was detected in 47.8% of individuals in the control group and in 76.1% of asthmatic patients. Individuals without the GSTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
3
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 23 publications
5
36
3
5
Order By: Relevance
“…These include polymorphic large deletions causing inactivation of two antioxidant genes, GSTM1 and GSTT1, that have previously been associated with several conditions where oxidative stress has been implicated. These include various forms of cancer (Strange et al, 2001), multiple sclerosis (Mann et al, 2000), ParkinsonÕs disease (Tan et al, 2000), asthma (Ivaschenko et al, 2002), and liver cirrhosis (Ghobadloo et al, 2004). For each of 5 other antioxidant genes, where no inactivating polymorphisms were present, several single nucleotide polymorphisms were used.…”
Section: Discussionmentioning
confidence: 99%
“…These include polymorphic large deletions causing inactivation of two antioxidant genes, GSTM1 and GSTT1, that have previously been associated with several conditions where oxidative stress has been implicated. These include various forms of cancer (Strange et al, 2001), multiple sclerosis (Mann et al, 2000), ParkinsonÕs disease (Tan et al, 2000), asthma (Ivaschenko et al, 2002), and liver cirrhosis (Ghobadloo et al, 2004). For each of 5 other antioxidant genes, where no inactivating polymorphisms were present, several single nucleotide polymorphisms were used.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 CNVs of the GST genes were examined in patients with atopic asthma and it was found that the null genotypes of GSTT1 and GSTM1 together with GSTP1 Val/Val polymorphism have a significant role in the asthma pathogenesis. 51 CNV AND CARDIOVASCULAR DISEASE Structural variations are also found to be affecting the susceptibility to many cardiovascular diseases.…”
Section: Cnv and Susceptibility To Other Common Disorders Hiv/aids Sumentioning
confidence: 99%
“…Asthma should be regarded as a multifactorial disease, involving both a genetic predisposition and environmental factors (Ivaschenko et al, 2002). The presence of inflammation in the airway is an important biochemical feature of asthma.…”
Section: Discussionmentioning
confidence: 99%